Pelatihan Penggunaan Teknologi Untuk Pengajaran Bagi Guru Bahasa Inggris di Kabupaten Kudus - Mali, Yustinus Calvin Gai (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
The trend of technological development in education encourages teachers to improve their professionalism as educators to know the latest technology tools and the potential they can maximize to support their teaching activities in their classrooms. In response to that situation, this community service (henceforth called PkM) activity in the form of guest lecture was held for 30 Madrasah English teachers at the Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA) levels in Kudus Regency. The guest lecture session was held on Tuesday, August 20, 2024, from 12.30-4.30 pm (Western Indonesia Time) at the Postgraduate Building, Universitas Muria Kudus. In the material presentation session under the guidance of the author as the speaker of the session, the participants had the opportunity to try directly and experience the potential of various technology tools, such as Famous People Lessons, Readlang, WordSift, ChatGPT, Google Gemini, and Google AI Studio, which they could use for English teaching activities in their language classrooms. Overall, the PkM ran smoothly, and the participants responded positively to the PkM session. Finally, the author shares some notes on continuing this PkM in the future.